Peluang pertumbuhan ekonomi di Kabupaten Majene Provinsi Sulawesi Barat - Sutisna, Muhammad Aziz Rizal (Environmental, Social, Governance and Sustainable Business, 2024)
Background: The high production of capture fisheries in Majene Regency is not balanced by a marketing system and infrastructure in the form of adequate fishing ports and fish processing units. Findings: It is recorded that currently Majene Regency only has 2 (two) fishing port units, namely PPI Palipi and PPP Banggae with a total of 30,887 fishermen, the largest in West Sulawesi out of a total of 57,318 people. With these conditions, the catch of Majene Regency fishermen is mostly sold in the middle of the sea. Methods: This paper uses a literature review method sourced from literature, such as scientific articles, books, journals, and online media. Conclusion: The number of fishing port infrastructure in Majene Regency is still relatively low when viewed from the amount of production in other regencies/cities in West Sulawesi Province. So a government policy step is needed as a form of support for economic growth that is in accordance with the potential in Majene Regency, one of which is fisheries. Thus, it is hoped that fishery products which are superior commodities can be distributed to areas that do not have the potential for capture fisheries resources or the exchange of commodities through a buying and selling system.